Evidence for coopetition at the maternal–fetal interface shaping placental invasion - Junaid Afzal; Yasir Suhail; Wenqiang Du; Yamin Liu; Ramalakshmi Ramasamy; Zukai Liu; Ruchi Goyal; Ashkan Novin; Sameera Suhail; Jamie Maziarz; Khadija Wali; Paul Robson; et al. (Proceedings of the National Academy of Sciences, 2025)
Coopetition is a term from game theory that describes a mix of cooperative and competitive behavior. The maternal–fetal interface (MFI) among eutherian mammals presents close interaction of two distinct individuals. These interactions have resulted in a remarkable diversity in MFI structure, often interpreted as the outcome of maternal–fetal conflict. Nevertheless, the fetus and the mother share evolutionary interests since 50% of fetal genes are maternal. In hemochorial species, characterized by invasive placentation, endometrial stromal fibroblasts (ESFs) undergo decidualization to regulate embryo implantation. In great apes, hemochorial placentation is driven by highly invasive extravillous trophoblast cells (EVT). Here, using EVTs differentiated from trophoblast stem cells, term placenta, as well as HTR8/SVneo, we demonstrate that EVTs orchestrate a transformation of the maternal stroma, reducing its resistance to invasion acquired during decidualization. Through paracrine signals, in particular IL-11, trophoblasts transform decidual ESFs from a matrix-producing to a matrix-degrading state. Notably, noninvasive cytotrophoblast cells, do not transform decidual ESFs. We further provide evidence that maternal coadaptation is critical to EVT-induced decidual transformation. Decidual ESFs upregulate expression of Suppressor of Cytokine Signaling 3 in response to EVTs, rewiring downstream IL-11 signaling from JAK/STAT to AP-1 specific transcription. We conclude that the evolution of highly invasive placentation is the outcome of both the evolution of invasive EVTs, as well as the evolution of maternal traits, i.e., the switch from JAK/STAT to AP-1 signaling. We interpret this as evidence for co-opetition (cooperation among competitors).